2021
DOI: 10.1139/bcb-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin reduces mycobacterial M1-type inflammation induced with trehalose 6,6′-dimycolate and facilitates the entry of fluoroquinolone into granulomas

Abstract: Primary Mycobacterium tuberculosis (Mtb) infection results in the formation of a densely packed granulomatous response that essentially limits entry and efficacy of immune effector cells. Furthermore, the physical nature of the granuloma does not readily permit entry of therapeutic agents to sites where organisms reside. The Mtb cell wall mycolic acid, trehalose 6,6’-dimycolate (TDM), is a physiologically-relevant molecule to model macrophage mediated events during establishment of the tuberculosis-induced gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Therefore, inhibiting the cytokine storm may be a prophylactic and therapeutic approach toward combating COVID-19 infection (Zimecki et al, 2021).In the study of pulmonary acute respiratory distress syndrome (ARDS) in granulomatous inflammation model (Mrityunjaya et al, 2020), it was found that LF can reduce or eliminate cytokine excess and pulmonary pathological features caused by Mycobacterium tuberculosis (Welsh et al, 2011;Hwang et al, 2017). In addition, LF was also able to diminish hyperacute immunopathology developed after the administration of isolated surface mycolic acid components (Nguyen et al, 2021(Nguyen et al, , 2022. LF significantly induced the expression of the antiviral immune response genes and partially inhibited SARS-CoV-2 infection and replication in Caco-2 intestinal epithelial cells to protect against SARS-CoV-2 infection in vitro (Salaris et al, 2021).…”
Section: Emerging Topicsmentioning
confidence: 99%
“…Therefore, inhibiting the cytokine storm may be a prophylactic and therapeutic approach toward combating COVID-19 infection (Zimecki et al, 2021).In the study of pulmonary acute respiratory distress syndrome (ARDS) in granulomatous inflammation model (Mrityunjaya et al, 2020), it was found that LF can reduce or eliminate cytokine excess and pulmonary pathological features caused by Mycobacterium tuberculosis (Welsh et al, 2011;Hwang et al, 2017). In addition, LF was also able to diminish hyperacute immunopathology developed after the administration of isolated surface mycolic acid components (Nguyen et al, 2021(Nguyen et al, , 2022. LF significantly induced the expression of the antiviral immune response genes and partially inhibited SARS-CoV-2 infection and replication in Caco-2 intestinal epithelial cells to protect against SARS-CoV-2 infection in vitro (Salaris et al, 2021).…”
Section: Emerging Topicsmentioning
confidence: 99%
“…Novel approaches to Mtb treatment include host-directed therapies ( Ndlovu and Marakalala 2016 ) which are focused in two major fronts; the first augments immune response using immune-based treatments ( Vilaplana et al 2013 ), while the second alters the resultant immunopathology ( Nguyen et al 2021 ). Examples of immune-based treatment methods include agents that target the macro-autophagic compartment, such as vitamin D and retinoic acid, which increase phagocytosis to enhance the lysosomal degradative processes inside macrophages ( Estrella et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Relative to the study described in this report, bovine lactoferrin significantlly reduced inflammatory pathology in Mtb -infected mice ( Welsh et al 2011 ). Both human and bovine lactoferrins were also shown effective to limit inflammation in a non-infectious TDM-induced granuloma mouse model ( Nguyen et al 2021 ; Welsh et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations